How learning-centred beliefs relate to awareness of educational identity and mission: An exploratory study among medical educators. (2nd December 2022) - Ottenhoff-de Jonge, Marleen W.; Steinert, Yvonne; van der Hoeven, Iris; Kramer, Anneke W. M.; van der Rijst, Roeland M.
Abstract: Introduction: Although learning-centred education would be most effective if all medical educators held learning-centred beliefs, many educators still hold teaching-centred beliefs. A previously developed theoretical model describes a relationship between beliefs, educational identity and 'mission, ' meaning that which inspires and drives educators. To increase our understanding of why educators hold certain beliefs, we explored the empirical relationship between educators' beliefs and their awareness of their educational identity and mission. Methods: A qualitative study was conducted using in-depth interviews with medical educators. We performed a deductive thematic analysis employing two existing models to examine educators' beliefs about teaching and learning and their awareness of their educational identity and mission. Results: Educators demonstrated both teaching-centred and learning-centred beliefs, which aligned with an awareness of their educational identity and mission. While educators who were un aware of both their identity and mission displayed teaching-centred beliefs, educators aware of their identity and mission displayed learning-centred beliefs. Those who were aware of their identity, but not their mission, displayed either teaching- or learning-centredness. Conclusions: Medical educators' awareness of identity and mission are related to their beliefs about education. Further research is needed into whether beliefs can change over time by increasing identity and mission awareness.